KONSEP PERTEMANAN DALAM ETIKA NIKOMAKEA ARISTOTELES (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
As social beings who live side by side with agreed behavioral norms, making the relationship between individuals has an important position, the relationship in question is known as the term friendship. With this important element in the concept of friendship, it is not surprising that Aristotle discusses it specifically in two books at once in his work entitled Nicomachean Ethics, and places the concept of friendship as the main and indispensable thing in life. This study aims to explain in order to know the concept of friendship contained in Aristotle Nicomachean Ethics. The method used by the author in this study is a descriptive-analytical method with a qualitative approach, and a library research data collection technique. The results of the research and discussion obtained in this study include the position of the concept of friendship, as well as the classification of friendship in Aristotle Nicomachean Ethics, especially in his VIII and IX books. It is said in his work, that no one will choose to live without a friend, even though he has been blessed with many good things in his life. So that in the concept of perfect or complete friendship according to Aristotle, namely the relationship between individuals who give each other good things, with reciprocity, and do it with full awareness. Aristotle said that if a friend is our other personal self, and what we get from a friend is a reflection of what we give too. Keyword: Aristotle, Friendship, Nicomachean Ethics.